2018
DOI: 10.3389/fpsyg.2018.02381
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Advice Discounting Occur? The Combined Roles of Confidence and Trust

Abstract: Judges tend to discount the opinions of others even though advice is often helpful in improving their accuracy. The present research proposes that this phenomenon of advice discounting results from the judges’ confidence in their initial decision and little trust in advice. Furthermore, the degree of advice discounting may be predicted by the combined roles of confidence and trust. Three studies provide evidence for these hypotheses. Participants were very confident in their initial estimation and had little t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…However, clear evidence for egocentric discounting has been found in both groups. Egocentric discounting was documented in Japanese [60,61] and Chinese participants [20,36,62], and in a group of executives from 24 different nationalities [28]. While some studies find stronger rates of egocentric discounting in East Asian participants as opposed to Western ones [61], others do not [20,60].…”
Section: Proximate Explanations For Egocentric Discountingmentioning
confidence: 99%
“…However, clear evidence for egocentric discounting has been found in both groups. Egocentric discounting was documented in Japanese [60,61] and Chinese participants [20,36,62], and in a group of executives from 24 different nationalities [28]. While some studies find stronger rates of egocentric discounting in East Asian participants as opposed to Western ones [61], others do not [20,60].…”
Section: Proximate Explanations For Egocentric Discountingmentioning
confidence: 99%
“…Situational factors play a role in whether individual trust and use advice. The decision to use a piece of advice relies on both confidence in one's beliefs and trust in the advice 33 . Generally, individuals overweight their own information and underweight the advice of others 34 .…”
Section: Advice Takingmentioning
confidence: 99%
“…Data preparation. Following Wang and Du (2018), trials were removed if the initial estimate matched the advice (novice advice: young ϭ 2.7%, older ϭ 2.3% of trials, t(110) ϭ 0.76, p ϭ .448, d ϭ .14; expert advice: young ϭ 3.4%, older ϭ 3.3% of trials, t(110) ϭ 0.08, p ϭ .939, d ϭ .01). This was because such trials cannot establish the degree to which participants used advice.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Taking advice involves cognitive processes such as initial valuation of the advice followed by the process of combining advice with individual judgment (Meshi, Biele, Korn, & Heekeren, 2012). Research involving young adults consistently shows that individuals adjust their independent estimates more toward (i.e., give more weight to) advice from experts than novices (e.g., Meshi et al, 2012; Sniezek & Buckley, 1995; Wang & Du, 2018). It is suggested that people value expert advice more than novice advice, and this valuation process takes place even before a decision is made and the outcome known.…”
mentioning
confidence: 99%